STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU ADMINITRASI PENDIDIKAN DI SD NEGERI KEBONSARI WETAN 1 KOTA PROBOLINGGO - Mujib Riduan; Wahidmurni; Parmujianto (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the strategies employed by the principal to improve the quality of educational administration at SD Negeri Kebonsari Wetan 1 in Probolinggo City. Effective educational administration is one of the key factors in achieving quality education goals. The principal, as a leader, plays an important role in designing and implementing the right strategies to enhance the quality of administration in the school. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with the principal, teachers, and administrative staff, as well as direct observation of administrative practices at the school. The findings show that the strategies applied by the principal include improving the competencies of administrative staff, utilizing technology in the administrative system, and strengthening communication between the school, parents, and the community. The most effective strategy found in this study was the principal's initiative to improve the competencies of administrative staff through targeted training, which significantly enhanced administrative performance. However, there are some challenges faced, such as limitations in human resources and budget. This study contributes to the development of managerial strategies that can be adapted by principals in other schools to improve the quality of educational administration. It is hoped that the results of this research can serve as a reference for education policymakers in formulating policies that support the improvement of administrative quality at the elementary school level.